Detection of Escherichia coli O157 in raw and cooked meat: comparison of conventional direct culture method and Enzyme Linked Fluorescent Assay (ELFA) (Italian Journal of Public Health, 2011)
Background: Verocytotoxin Escherichia coli is a frequent and important cause of diarrhea and haemolyticuremic syndrome all over the world. Consumption of ground beef, lettuce, and other kinds of food havebeen associated with outbreaks,The aim of this study was to detect the presence of E. coli O157 in meat products collected from hospitalfood catering services in Rome, using a rapid detection method in comparison with a standard culturemethod to verify the effectiveness of HACCP system.Methods: Three hundred and ten food samples (80 of cooked and 230 of raw meat) were screenedfor E.coli O157 by ISO culture method and by enzyme-linked-fluorescent-assay (ELFA)-based methods(VIDAS®system, bioMérieux). All isolates obtained were tested for VT1 and VT2 genes by PCR. Thestatistical analysis considered absolute frequencies and percentages. The K statistic was applied to assessagreement between direct culture method and the VIDAS system.Results: A total of 6 (1,9%) E.coli O157 isolates were recovered from raw meat samples by the culturemethod; of these only four were identified by PCR as VTEC producers. A total of 9 (2,9%) E.coli O157isolates were recovered from raw meat samples by the VIDAS® system. No E.coli O157 was detectedin cooked products. All comparisons between the direct culture method and the VIDAS system werestatistically significant (K= 0,795; p
Keywords: VTEC O157; ELFA; PCR; hospital food service